Crystallization behavior of diblock copolymers based on PCL and PLLA biopolymers. (1st December 2014) - Navarro‐Baena, Iván; Marcos‐Fernandez, Angel; Kenny, José M.; Peponi, Laura
<x xml:space="preserve">Abstract</x> This paper aims to increase the knowledge on the crystallinity features of diblock copolymers based on poly(ɛ‐caprolactone) (PCL) and poly(L‐lactic acid) (PLLA). Six diblock copolymers have been synthesized starting from a synthesized PCL with a molecular weight of around 5000 g mol−1, varying the molecular weight of the PLLA block. The crystalline unit cells for both PCL and PLLA blocks have been studied with wide‐angle X‐ray diffraction analysis. The effects of the copolymer composition on the crystalline cell parameters as well as on the degree of crystallinity and the crystallite sizes, determined using the Scherrer equation, are discussed. The double‐crystalline nature of the diblock copolymer was confirmed by small‐angle X‐ray scattering experiments. This technique was also used to study the melting behavior of the copolymers by studying the variation of the diffraction spectra with temperature. The effects of PCL chains on the packing of the PLLA lamellae are discussed. Finally, the crystallization behavior was studied by differential scanning calorimetry analysis, performing experiments at different crystallization temperatures and studying the results by fitting the experimental data with an Avrami‐type equation. The influence of each block on the crystallization parameters of the other block are discussed. This study allows a better understanding of the effects of the chemical structure on the crystalline behavior of these block copolymers, leading to the possibility to tailor the materials for specific applications.